Indentation and flattening of rough surfaces spherical asperities - Ogar, Petr; Gorokhov, Denis; Ugryumova, Elena (International Journal of Engineering and Technology, 2018)
The paper indicates that the application of roughness models and the theories of contacting rough surfaces developed by Greenwood-Williamson and N.B. Demkin for solving the problems of hermetology leads to significant errors. This is explained by much greater contact pressures than for the tribology problems, by describing only the initial part of the reference surface curve, the lack of allowance for the plastic extrusion of the material. A brief review of methods for describing the introduction of a sphere into an elastoplastic reinforced half-space is given. The properties of the elastoplastic reinforced material are described by the power law of Hollomon. To describe the indentation and flattening of single spherical asperity, the results of finite element modeling are used. The cases of contacting a rigid rough surface with an elastoplastic half-space and a rigid smooth surface with a rough surface are considered. To determine the relative contact area, the discrete roughness model is used in the form of a set of spherical segments distributed along the height in accordance with the curve of the reference surface.Â